Odpowiedź :
2) -2 - (4 - 3x) = -7
-2 - 4 + 3x = -7
-6 + 3x = -7
3x = -7 + 6
3x = -1 /:3
x = - 1/3
3) 2(13 - x) - 9 = 1
26 - 2x - 9 = 1
17 - 2x = 1
-2x = 1 - 17
-2x = -16 /:(-2)
x = 8
4) 5 - (3 - 4x) = 5(1-x)
5 - 3 + 4x = 5 - 5x
2 + 4x = 5 - 5x
4x + 5x = 5 - 2
9x = 3 /:9
x = [tex]\frac{3}{9}[/tex]
x = [tex]\frac{1}{3}[/tex]
5) [tex]\frac{y}{3} + \frac{y}{8} = \frac{1}{6}[/tex] /*24
8y + 3y = 4
11y = 4 /:11
y = [tex]\frac{4}{11}[/tex]
Odpowiedź:
-6x=-15+3
-6x=18//:(-6)
x=-3
2)
-2-4+3x=-7
3x=-7+2+4
3x=-1//:3
x=-1/3
3)
26-2x-9=1
-2x=1-26+9
-2x=-16//:(-2)
x=8
4)
5-3+4x=5-5x
5x+4x=5-5+3
9x=3//:9
x=1/3
Szczegółowe wyjaśnienie:
5 nie mogę bo mam quiz do zrobienia